2016
DOI: 10.1002/dmrr.2790
|View full text |Cite
|
Sign up to set email alerts
|

Association between intestinal permeability and faecal microbiota composition in Italian children with beta cell autoimmunity at risk for type 1 diabetes

Abstract: The results of this study validated the hypothesis that increased intestinal permeability together with differences in microbiota composition are contemporaneously associated with the pre-pathological condition of T1D in a sample of Italian children. Further studies are necessary to confirm the microbial markers identified in this sample of children as well as to clarify the involvement of microbiota modifications in the mechanisms leading to increased permeability and the autoimmune mechanisms that promote di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 41 publications
2
62
0
2
Order By: Relevance
“…metagenomic relative abundance) coincide with an increase in contributions from P. merdae in the total transcript pool. This behavior is in contrast with that of Dialister invisus : a bacterium predominantly associated with the human oral cavity, which has also been detected in the gut and been implicated in diseases such as IBD and type-1 diabetes 22 , 27 , 28 . While the average DNA abundance of D. invisus was comparable to that of P. merdae , and varied across samples, D. invisus was largely absent from our metatranscriptomic data ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…metagenomic relative abundance) coincide with an increase in contributions from P. merdae in the total transcript pool. This behavior is in contrast with that of Dialister invisus : a bacterium predominantly associated with the human oral cavity, which has also been detected in the gut and been implicated in diseases such as IBD and type-1 diabetes 22 , 27 , 28 . While the average DNA abundance of D. invisus was comparable to that of P. merdae , and varied across samples, D. invisus was largely absent from our metatranscriptomic data ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Maffeis and colleagues chose 10 healthy subjects and 10 children at risk for T1D to participate in a case‐control study to examine the relationship between intestinal permeability and T1D. The results showed that 3 bacteria, including Dialister invisus , Gemella sanguinis , and Bifidobacterium longum, were associated with altered intestinal permeability in T1D . In addition, many other studies revealed that the changes of certain microbes, such as Clostridium perfringens , Dialister invisus , Gemella sanguinis , and Bifidobacterium longum , were related to compromised gut integrity and increased T1D risk .…”
Section: Gut Microbiome and Type 1 Diabetesmentioning
confidence: 96%
“…The results showed that 3 bacteria, including Dialister invisus , Gemella sanguinis , and Bifidobacterium longum, were associated with altered intestinal permeability in T1D . In addition, many other studies revealed that the changes of certain microbes, such as Clostridium perfringens , Dialister invisus , Gemella sanguinis , and Bifidobacterium longum , were related to compromised gut integrity and increased T1D risk . When the intestinal permeability is increased, intestinal toxins, food antigens, and infection factors may translocate from gastrointestinal lumen to intestinal mucosal components, and finally to the pancreatic lymph nodes to induce or exacerbate T1D …”
Section: Gut Microbiome and Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of obese and non-obese diabetic mice have observed that this leads to increased cytokine production that may attack and damage pancreatic β-cells. [57][58][59] Bacterial metabolites may also attack the pancreatic islet directly. This was shown during a study of mice in which Streptomyces-derived toxins impaired glucose tolerance, reducing islet size and β-cell mass at low doses via adenosine triphosphatase inhibition.…”
Section: Mechanistic Linksmentioning
confidence: 99%